Pathophysiology of the right ventricle and of the pulmonary circulation in pulmonary hypertension: an update. Issue 1 (24th January 2019) - Vonk Noordegraaf, Anton; Chin, Kelly Marie; Haddad, François; Hassoun, Paul M.; Hemnes, Anna R.; Hopkins, Susan Roberta; Kawut, Steven Mark; Langleben, David; Lumens, Joost; Naeije, Robert
The function of the right ventricle determines the fate of patients with pulmonary hypertension. Since right heart failure is the consequence of increased afterload, a full physiological description of the cardiopulmonary unit consisting of both the right ventricle and pulmonary vascular system is required to interpret clinical data correctly. Here, we provide such a description of the unit and its components, including the functional interactions between the right ventricle and its load. This physiological description is used to provide a framework for the interpretation of right heart catheterisation data as well as imaging data of the right ventricle obtained by echocardiography or magnetic resonance imaging. Finally, an update is provided on the latest insights in the pathobiology of right ventricular failure, including key pathways of molecular adaptation of the pressure overloaded right ventricle. Based on these outcomes, future directions for research are proposed. State of the art and research perspectives in pathophysiology of the right ventricle and of the pulmonary circulation in pulmonary hypertension with theoretical and practical aspects http://ow.ly/18v830mgLiP